The Correlation of Waist Circumference, Uric Acid Levels, Random Blood Glucose with Blood Pressure Among Elderly in Bukit Kemuning - Fatmawati Fatmawati; Desti Ambar Wati; Masayu Dian Khairani; Amali Rica Pratiwi (Universitas Airlangga, 2026)
Background: In elderly individuals, high blood pressure causes hyperglycemia, resulting in insulin resistance and endothelial dysfunction. The presence of metabolic disorders, including increased random blood glucose and uric acid levels, results in hypertension among elderly individuals through distinct vascular and metabolic pathways. Objectives: This study examined the effects of random blood glucose and uric acid levels and waist circumference on blood pressure among elderly people at the Bukit Kemuning Inpatient Public Health Center. Methods: A cross-sectional approach was used, and 169 participants were selected through purposive sampling. The research instruments comprised an observation sheet, a GCU 3-in-1 Easy Touch device for measuring uric acid and blood glucose levels, a Minar digital scale that measured body weight with 0.1 kg accuracy, and a calibrated Minar stadiometer that measured height with 1 mm precision. Waist circumference data were obtained from secondary data in the elderly registry. Data analysis was performed using the Spearman Rank correlation test. Results: Statistical analysis showed significant but weak correlations between waist circumference (p=0.000; r=0.350), uric acid levels (p=0.000; r=0.267), and random blood glucose levels (p=0.001; r=0.257) with blood pressure in the elderly. Conclusion: Waist circumference, uric acid levels, and random blood glucose levels were weakly associated with systolic blood pressure among elderly individuals in the working area of the Bukit Kemuning Inpatient Public Health Center. Therefore, these metabolic factors should be considered in strategies for the prevention and control of hypertension in the elderly population.